Confusion Effects of Facial Expression Recognition in Patients With Major Depressive Disorder and Healthy Controls - Mo, Fan; Gu, Jingjin; Zhao, Ke; Fu, Xiaolan (Frontiers in Psychology, 2021)
Facial expression recognition plays a crucial role in understanding people’s emotion, as well as in social interaction. Patients with Major Depressive Disorder (MDD) have been repeatedly reported to be impaired in recognizing facial expressions. The present study aimed to investigate the confusion between two facial expressions which presented different emotions and compare the difference of confusion effect for each emotion pair between MDD patients and healthy controls. Participants were asked to judge the emotion category of each facial expression in a two-alternative forced choice paradigm. Six basic emotions (i.e., happiness, fear, sadness, anger, surprise, and disgust) were examined in pairs, resulting in 15 emotion combinations. Results showed that MDD patients were impaired in the recognition of all basic facial expressions except for the happy expression. Moreover, MDD patients were more inclined to confuse a negative emotion (e.g., anger and disgust) with another emotion as compared to healthy controls. These findings highlight the importance that MDD patients show the deficit of sensitivity in distinguishing specific two facial expressions.